Recent Patents on Boiler Burners for Natural Gas - Yang, Daolong; Li, Jianping; Wang, Yanxiang; Tian, Chao; Zhang, Chi (Recent Patents on Mechanical Engineering, 2019)
Background: With the development of natural gas and shale gas worldwide, the consumption of gas will continue to increase in the future. Natural gas is flammable and explosive, and the exhaust gas produced during the combustion of natural gas in boiler burners is one of the main sources of NOx in the air. Objective: This paper introduces patents and researches of natural gas boiler burners to improve the safety of natural gas boiler burners and reduce the emission of nitrogen oxides. Methods: In summarizing the existing boiler burner for natural gas, this paper introduces three new patents of natural gas boiler burner: the low-nitrogen burner, the energy-saving leakage-detecting burner and the small boiler burner. Results: The low-nitrogen burner identifies the fixed control of gas flow, enhances the gas flow's antiinterference ability, and achieves a relatively accurate ratio of the fuel-air flow. The energy-saving leakage-detecting burner enhances the natural gas and air flow stability and improves combustion efficiency and the safety and reliability by optimizing the ratio of natural gas to air. The small boiler burner improves the safety and reliability of the natural gas boiler burner, prolongs the service life of the igniter, and makes up for the shortcomings of high stability in the gas pressure. Conclusion: On the basis of ensuring the safety of the burner, the low-nitrogen transformation of the boiler burner is as energy-efficient as possible in order to maximize the advantages of natural gas resources.
Keywords: natural gas